ANALISIS TRANSMISI HARGA DUNIA KAKAO BIJI KE TINGKAT PETANI DESA SIMPANG II KECAMATAN SIMPANG RAYA KABUPATEN BANGGAI PROVINSI SULAWESI TENGAH - Anggraini, Tetik; Yantu, M.R; Kalaba, Yulianti (AGROTEKBIS, 2016)
The aims of this study were to identify the form of price relationship at different level of cocoa bean markets from the world market to the farmer market, to analyse the integration of the cocoa bean markets, and to analyse the transmission elasticity of cacao bean price. The location of this study was purposively selected. Sampling technique used was simple random sampling. There were 30 farmers interviewed. Analysis model used was regression and correlation analysis. Results of the analysis showed that the form of price relationship between the world market and the farmer market depend on market structures. These relationships involved some market levels, from the world markets, Indonesian markets, Palu central market, regency market to farmer market. Results of the analysis on the form of cacao bean price relationship between the world market and the farmer market was positive and significant. Integration of world cacao bean markets and farmer markets in Simpang II village was strong and significant. This was indicated by a high correlation value, in average r = 0.895. Regression coefficient (Î²) was less than one which means that the trasmission elasticity of cacao bean prices from the world markets to farmer markets was inelastic. Therefore, market structures formed was unfully competitive markets. However, the transmission elasticity of the cacao bean price was still high.Key Words: Cacao beans, market, price transmission.